(untitled) (Asian Journal of Social Science Studies, 2024)
This study applies the Unified Theory of Acceptance and Use of Technology (UTAUT) to understand consumer behavior in the hydraulic elevator market. Emphasizing Performance Expectation (PE) and Effort Expectation (EE), the research highlights hydraulic elevators’ reliability and ease of maintenance as key factors influencing consumer preferences. Contrary to conventional UTAUT findings, Social Influence (SI) is less influential compared to practical considerations such as cost and efficiency. A comprehensive feasibility analysis identified strong technical and operational feasibility for hydraulic elevators, but raised concerns in legal and scheduling aspects, indicating potential adoption barriers. The study’s comparative analysis with newer elevator technologies provides insights into consumer preferences across different elevator systems. The findings have significant implications for industry stakeholders, suggesting the need for focused marketing strategies and streamlined regulatory frameworks. This research contributes to a deeper understanding of the hydraulic elevator market, underscoring the importance of adapting technology adoption models to specific industry contexts.